Static Structural Analysis of Different Spoke Thickness on Vehicle Wheel Rim - Muhammad, Muhaimin; MAHMUDIN, RAHMAH (Progress in Engineering Application and Technology, 2021)
A wheel rim is a very important part for the whole system of a transportation. A lot of impacts and loads acting on them when the vehicle was use on the road. They had to go through the outside force of resistances on the road and hold the pressure of the whole weight of the vehicle. It is important to design a wheel rim so it can take such impacts and pressure for the safety of the vehicle itself and the passengers inside. That’s are the main criteria of a wheel rim. For this research, a wheel rim will be design and an analysis of impacts will be done towards the designed rim. So, there will be three different design of wheel rims with the same material and overall dimensions but the spokes thickness are different from one another. The rim will be designed using Solidworks 2019 software. The analysis of impacts will be done using ANSYS 2019 R3 software where the method of finite element analysis (FEA) take places. Using the same amount of impacts, there will be two type of impacts that are the force and pressure. Apply on all the three wheel rim designs with the same amount of magnitude at the same exact contact surface. The force will be 100 Newton and the pressure is 1 MPa. The criteria of the rim simulation will be involving the total deformation, equivalent elastic strain and equivalent stress. From the results, a comparison of the three will rim can be done to see their behaviour towards the impacts given. From there, it can be determine which design has the best criteria for a wheel rim and exactly why is that rim is chosen based on the analysis that been made.